Similar stage-dependent survival and outcome in sporadic and hereditary medullary thyroid carcinoma - Raue, Friedhelm; Bruckner, Thomas; Frank-Raue, Karin (The journal of clinical endocrinology & metabolism, 2021)
Long-term data are scarce on large cohorts with sporadic (sMTC) and hereditary medullary thyroid carcinoma (hMTC).To compare long-term disease-specific survival (DSS) and outcomes between sMTC and hMTC groups.Retrospective analysis.German tertiary referral center.A total of 673 patients with MTC that underwent surgery from January 1974 to July 2019.None (observational study).Differences between sMTC and hMTC in long-term, stage-dependent survival and outcomes.Surgery was performed at median ages of 49 years for sMTC (n = 477, 44% male) and 29 years for hMTC (n = 196, 43% male; P < 0.0001). The mean follow-up times were 9.2 ± 8.0 (sMTC) and 14.6 ± 10.3 years (hMTC). Age and tumor stage at diagnosis were significantly different between the 2 groups (P < 0.0001). The sMTC and hMTC groups had different overall DSS (log rank, P = 0.0183), but similar stage-dependent DSS (log rank, P = 0.1242-0.8981). In a multivariate analysis, sMTC and hMTC did not differ in DSS (hazard ratio [HR] = 1.56; 95% CI, 0.94-2.57), but in both groups, a worse DSS was significantly associated with age at diagnosis (HR = 1.04; 95% CI, 1.02-1.05), male sex (HR = 0.49; 95% CI, 0.32-0.76), and stages III and IV at diagnosis (HR = 20.00; 95% CI, 2.74-145.91 and HR = 97.47; 95% CI, 13.07-726.67, respectively). The groups had significantly different (P < 0.0001) outcomes (i.e., cured, minimal residual disease, structural detectable disease, and death), but similar stage-dependent outcomes (P = 0.9449-0.0511), except for stage III (P = 0.0489).Patients with sMTC and hMTC had different ages of onset, but similar stage-dependent DSS and outcomes after the MTC diagnosis. This finding suggested that tumor behavior was similar in sMTC and hMTC.
Gesehen am 18.10.2021